“NOBODY LOOKS AT THESE WORKERS”: THE PRECARIOUS WORK OF THE AGENTS OF DEATH MARKET AND THE PANDEMIC OF COVID-19 IN THE RIO DE JANEIRO STATE - da Silva, Rosana Oliveira; Nascimento, Rejane Prevot; Barros, Denise Franca; André, Robson Gomes (Revista Brasileira de Estudos Organizacionais, 2025)
The objective of this research was to discuss the worsening of the characteristics of precarious work in the activity of workers who work in the sale of products and in the provision of various services related to the management of death, as a result of the pandemic of the new coronavirus. The present work originated from data collected in the period prior to the outbreak of Covid-19. However, in order to achieve the objective, reports extracted from in-depth interviews with market workers in the city of Rio de Janeiro, carried out before the pandemic, and the articles of a newspaper of great circulation in the same city, during the pandemic, were analyzed. As results, it is possible to notice the accentuation of existing precariousness and new precariousness, such as high health risk and suffering at work. We conclude with some proposals to reduce existing precariousness.